SCIENTIFIC APPROACH-BASED OF INTERACTIVE LEARNING MEDIA TO IMPROVE MATHEMATICAL THINKING SKILL AND SELF-REGULATED LEARNING - NANI RATNANINGSIH; EDI HIDAYAT; R. REZA EL AKBAR (Sriwijaya University Learning and Education International Conference, 2016)
The aim of this research is to write a learning book and to develop a software of interactive media based on scientific approach to facilitate students in discovering concept, improving their mathematical thinking skill, and self-regulated learning. This is a two-year Research and Development, whereas in the first year is to write textbooks, and develop a interactive media software. The second year is to measure the validity of the entire instrument, the pre-test and post-test mathematical thinking skill, implement the software in a learning process, distribution a self-regulated learning questionnaire, implement the software in a learning process, explore the students’ perception towards this software through interviews. The sample of this research is seven grade students of junior high school in Tasikmalaya. Two schools are selected randomly. The developing of this software complies of stages: concept, design, material collecting, assembly, testing, and distribution. The validity test of all instrument used consists of consideration of two experts (a mathematician and learning-media expert); revision based on advices and input from both experts, empirical trial test, revision further if necessary. Based on the results of consideration two experts of instructional media and mathematician, test empirically, and perceptions of students that textbooks, textbook and software interactive learning media based approach to scientific, worthy implemented in the learning of mathematics students at the junior high school.